Core–Shell FeSe2/C Nanostructures Embedded in a Carbon Framework as a Free Standing Anode for a Sodium Ion Battery. Issue 47 (3rd November 2020) - Yousaf, Muhammad; Wang, Zhipeng; Wang, Yunsong; Chen, Yijun; Ali, Usman; Maqbool, Muhammad; Imran, Ali; Mahmood, Nasir; Gao, Peng; Han, Ray P. S.
Abstract: Embedding the functional nanostructures into a lightweight nanocarbon framework is very promising for developing high performance advanced electrodes for rechargeable batteries. Here, to realize workable capacity, core–shell (FeSe2 /C) nanostructures are embedded into carbon nanotube (CNT) framework via a facile wet‐chemistry approach accompanied by thermally induced selenization. The CNT framework offers 3D continuous routes for electronic/ionic transfer, while macropores provide adequate space for high mass loading of FeSe2 /C. However, the carbon shell not only creates a solid electronic link among CNTs and FeSe2 but also improves the diffusivity of sodium ions into FeSe2, as well as acts as a buffer cushion to accommodate the volume variations. These unique structural features of CNT/FeSe2 /C make it an excellent host for sodium storage with a capacity retention of 546 mAh g −1 even after 100 cycles at 100 mA g −1 . Moreover, areal and volumetric capacities of 5.06 mAh cm −2 and 158 mAh cm −3 are also achieved at high mass loading 16.9 mg cm −2, respectively. The high performance of multi‐benefited engineered structure makes it a potential candidate for secondary ion batteries, while its easy synthesis makes it extendable to further complex structures with other morphologies (such as nanorods, nanowires, etc.) to meet the high energy demands. Abstract : A free standing electrode (CNT/FeSe2 /C) with double cage protection is presented for sodium ion battery (SIB). The high porosity in the CNT/FeSe2 /C structure results in densified framework upon compaction while dual carbon protection buffers the volume changes upon battery cycling. These features make CNT/FeSe2 /C anode for practical application with high gravimetric, areal, and volumetric capacities along with good cyclic stability.